2020
DOI: 10.1097/ta.0000000000002659
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic injury patterns in blast: Morbidity and mortality

Abstract: BACKGROUND Pelvic trauma has emerged as one of the most severe injuries to be sustained by the victim of a blast insult. The incidence and mortality due to blast-related pelvic trauma is not known, and no data exist to assess the relative risk of clinical or radiological indicators of mortality. METHODS The UK Joint Theater Trauma Registry was interrogated to identify those sustaining blast-mediated pelvic fractures during the conflicts in Iraq and Afgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
0
16
0
4
Order By: Relevance
“…Limb flail has been shown in an animal model to be linked to traumatic amputation (Rankin et al, 2019). However, the traumatic amputation rates seen in the animal study were far lower than what is seen in battlefield data (Rankin et al, 2019(Rankin et al, , 2020. When a pre-test crush was applied to the thigh causing soft tissue disruption, all mice subsequently sustained traumatic amputations following lower limb flail in simulated blast-wave conditions (Rankin et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Limb flail has been shown in an animal model to be linked to traumatic amputation (Rankin et al, 2019). However, the traumatic amputation rates seen in the animal study were far lower than what is seen in battlefield data (Rankin et al, 2019(Rankin et al, , 2020. When a pre-test crush was applied to the thigh causing soft tissue disruption, all mice subsequently sustained traumatic amputations following lower limb flail in simulated blast-wave conditions (Rankin et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Lower limb flail (tertiary blast injury) has been hypothesized to cause pelvic bony displacement following the initial fracture with subsequent displacement of the intrapelvic soft tissues causing pelvic vascular injury (Rankin et al, 2019). Military clinical data have shown that pelvic vascular injury occurs predominately at the posterior pelvis, with significant retroperitoneal bleeding (Rankin et al, 2020). It was identified as the injury with the single greatest risk of mortality in the dismounted pelvic blast injury casualty, followed by traumatic amputation (Rankin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations